2020
DOI: 10.1111/jce.14480
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of adjunctive posterior wall isolation in persistent atrial fibrillation: A meta‐analysis

Abstract: Background: Pulmonary vein isolation (PVI) is the cornerstone of atrial fibrillation (AF) ablation but the recurrence rate remains relatively high in persistent patients with AF. Therefore, posterior wall isolation (PWI) in addition to PVI has been proposed to increase freedom from AF.Objective: To evaluate the success of adjunctive PWI in persistent AF. Methods:We searched electronic database using specific terms. The primary outcomes are recurrence rate of AF and recurrence of atrial arrhythmias. The seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 34 publications
2
25
0
1
Order By: Relevance
“…Consistent with preclinical data, a recent meta‐analysis 18 reported that adjunctive LAPWI in PersAF resulted in a significant reduction in the recurrence rate of ATas, without an increased risk of atrial flutter, compared to patients who had PVI only. Noticeably, only in one of the included studies PVI and LAPWI were performed with a second‐generation CB‐A and few studies focusing on LAPWI with CB‐A have been published so far.…”
Section: Discussionsupporting
confidence: 54%
“…Consistent with preclinical data, a recent meta‐analysis 18 reported that adjunctive LAPWI in PersAF resulted in a significant reduction in the recurrence rate of ATas, without an increased risk of atrial flutter, compared to patients who had PVI only. Noticeably, only in one of the included studies PVI and LAPWI were performed with a second‐generation CB‐A and few studies focusing on LAPWI with CB‐A have been published so far.…”
Section: Discussionsupporting
confidence: 54%
“…The majority of these studies included only patients with PersAF and LSPersAF, which is in line with current guideline recommendations when considering posterior wall isolation in conjunction with PVI [ 1 ]. Meta-analyses of a few randomised and observational comparison studies have suggested an overall benefit of endocardial posterior wall ablation compared to pulmonary vein isolation alone in PersAF [ 35 , 36 ], but results of the individual studies, including the randomised clinical trials [ 37 , 38 , 39 ], are mixed ( Table 1 ). This may, in part, be due to the lack of a standardised approach to posterior wall isolation, which is evidenced by the various lesion sets used in published studies.…”
Section: The Posterior Wall Of the Left Atrium In Non-paroxysmal Atrial Fibrillationmentioning
confidence: 99%
“…Pulmonary vein isolation (PVI) has become the standard treatment for atrial fibrillation (AF) and some studies have reported the benefits of additional posterior wall isolation (PWI) after PVI for persistent AF, which they had confirmed by meta-analysis. 1 However, a previous study reported that PWI in addition to PVI did not improve the recurrence of AF. 2 Furthermore, PWI with additional ablation within the box lesion from 41% to 55% after roof and inferior line ablation has been reported.…”
Section: Residual Potential At the Epicardial Left Atrium After Convementioning
confidence: 92%